ReaxFF Molecular Dynamics Simulations of Water Stability of Interpenetrated Metal-Organic Frameworks - Liu, Xiu Ying; Pai, Sung Jin; Han, Sang Soo (American Chemical Society, 2017)
Molecular dynamics (MD) simulations using the reactive force field (ReaxFF) have been performed to elucidate the underlying water-induced disruption mechanism of several prototypical interpenetrated MOFs (IRMOF-9, IRMOF-13, and SUMOF4). Through the comparison to the corresponding noninterpenetrated MOFs (IRMOF-10 and IRMOF-14), for both the interpenetrated and noninterpenetrated MOFs, structural collapse was always accompanied by the dissociation of the water molecules, with the produced OH- and H+ forming chemical bonds with the Zn2+ ion and O atom of the ligand, respectively. However, the water stability of the interpenetrated MOFs is less than that of the corresponding noninterpenetrated structures. The reasons for the differences between the MOFs in the resistance to water attack are clarified. The water resistance of the noninterpenetrated MOFs is mainly attributed to the strength of the Zn-O-ligand, but, the hydrogen bond has little effect. However, a trade-off between the strength of the Zn-O-ligand bond and the hydrogen bond determines the water stability of the interpenetrated MOFs. We expect that our understanding of the water-disruption mechanisms of MOFs will provide helpful guidance for the design of MOFs with a high water-resistance. Additionally, this work shows that ReaxFF simulations could be a useful technique for predicting the hydrothermal stability of MOFs.
Keywords: REACTIVE FORCE-FIELD; CARBON-DIOXIDE CAPTURE; HYDROGEN STORAGE; ADSORPTION; MECHANISM; LIGANDS; NI